7(x+4)-3(x+6)=19

Simple and best practice solution for 7(x+4)-3(x+6)=19 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(x+4)-3(x+6)=19 equation:


Simplifying
7(x + 4) + -3(x + 6) = 19

Reorder the terms:
7(4 + x) + -3(x + 6) = 19
(4 * 7 + x * 7) + -3(x + 6) = 19
(28 + 7x) + -3(x + 6) = 19

Reorder the terms:
28 + 7x + -3(6 + x) = 19
28 + 7x + (6 * -3 + x * -3) = 19
28 + 7x + (-18 + -3x) = 19

Reorder the terms:
28 + -18 + 7x + -3x = 19

Combine like terms: 28 + -18 = 10
10 + 7x + -3x = 19

Combine like terms: 7x + -3x = 4x
10 + 4x = 19

Solving
10 + 4x = 19

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-10' to each side of the equation.
10 + -10 + 4x = 19 + -10

Combine like terms: 10 + -10 = 0
0 + 4x = 19 + -10
4x = 19 + -10

Combine like terms: 19 + -10 = 9
4x = 9

Divide each side by '4'.
x = 2.25

Simplifying
x = 2.25

See similar equations:

| 2x+(3x-4)=(2x-3) | | 1+(1)(1)= | | (1)(1)+1= | | 9x-7=-3x+29 | | -1.4121-(1-2.4)= | | 4+(2)(3)= | | 4(2+3)= | | 7x-14=-3x+6 | | 3(x-1)(x+1)=9 | | 7+(1)(-2)= | | 7(1)+(-2)= | | 7(1+-2)= | | 3(2x-1)=4(x+2) | | 7(7x-2)=49x-14 | | -5+2(4)= | | -5(2)+4= | | y-4=-2/3x | | -5(1-2n)=15 | | -5(2+4)= | | 9x+7=-5+7x+16 | | -3(t+3)=15 | | 47-15=4(x-6) | | 70+5y-32=17y-11-5y | | 2+(-3)(4)= | | (36m-9mn=45n)/9 | | k^2+2k+-60=0 | | -4(p+5)= | | 4(2x+9)=-7x-24 | | 2(-3+4)= | | 50+3x= | | 5=-5a+2a | | 4(k+0.5)=2k+k+6 |

Equations solver categories